(untitled) (FUDMA JOURNAL OF SCIENCES, 2022)
The study is aimed at investigating the effect of alcohol intake on gut microbiota and antibiotic susceptibility of some of the microbial genera isolated. Twenty-four wistar rats were administered orally with branded dry gin (40% alcohol) and one was picked randomly every 48hrs and sacrificed by cervical decapitation. The intestine was collected aseptically after laparotomy and placed in a sterile petri dish. The intestinal bacteria were enumerated, isolated and identified using standard microbiological methods. The antibiotic susceptibility was done using the disc agar diffusion method. The Total Heterotrophic (x 104 CFU/g) and Total Coliform Counts ranged from 2.0 – 65 and 1 – 28 respectively. Bacteria genera isolated are; Escherichia, Proteus, Citrobacter, Lactobacillus, Enterococcus, Enterobacter, Salmonella, Klebsiella and Bacillus. E. coli was the most (100%) prevalent. Enterococcus, Lactobacillus and Enterobacter were also highly prevalent. The occurrence of the genera was in the order Lactobacillus > Citrobacter > Klebsiella and Salmonella > Proteus. All isolates were present in all the intestines few days after administration of the gin, but there was a decline in the occurrence till the 21st day, after which there was an increase. The susceptibility of Escherichia to conventional antibiotics was between 0–90% and there was no particular trend with the length of exposure but there was substantial decrease in the susceptibility to the antibiotics. The susceptibility of Enterococcus to the antibiotics decreased with the length of exposure to the alcohol. Intake of alcohol has a pronounced effect on the gut microbiome and the antibiotic susceptibility of isolates.